Autoridades religiosas e mediasferas: reconfigurações na viragem do século XXI - Teixeira, Alfredo (Lusitania sacra, 2025)
The modern mediaspheres became a favourable environment for the proliferation of religious worldviews, which cannot be understood within the strict limits of orthodoxies and orthopraxies. Furthermore, the explosion of mass media in the second half of the 20th century and the development of social media at the beginning of the 21st century greatly impacted reshaping forms of religious authority. In this essay, we start by observing two historical contexts - the communicational strategies of Pope John Paul II and the dynamics of Islamic cyberspace - to test a theoretical framework that allows a comparative approach to religious phenomena in the context of different communicational ecosystems. This essay aims to provide a point of view on the interpretative models emerging in the context of the reconfigurations that, at the end of the 20th century and the beginning of the 21st, are taking shape in the correlations being woven between religious authority and the different mediaspheres.